Strengthening the Primary Mathematics Teacher's Self-Efficacy Through Online Professional Learning Communities - Saragih, Melda Jaya; Listiani, Tanti; Seleky, Jacob Stevy; Tamba, Kimura Patar; Nagaratnam, Shalini (FKIP Universitas Lampung, 2025)
The perseverance, characteristics, and competencies of teachers can enhance the professional quality, motivation, and attitude of mathematics teachers. Recognizing the significance of professional development and personal growth for elementary school mathematics teachers, a Professional Learning Community (PLC) was implemented. This study aims to examine the impact of online PLC on teachers' self-efficacy in teaching mathematics. The research method used was mixed methods, quantitative and qualitative research. Data was collected by survey and interviews with 16 6th-grade mathematics teachers at Lentera Harapan School (SLH) in Indonesia. The questionnaire data were analysed by the Wilcoxon test, and the interview results were analysed qualitatively. The results find that after being given online PLC, there was a significant increase in teacher self-efficacy in teaching mathematics. Teachers respond positively to this activity because they can collaborate with other teachers from various elementary schools and support each other in their professional development. Teachers enjoyed the session of sharing experiences in overcoming learning difficulties faced by students in class. Thus, teachers' self-efficacy can be strengthened by ongoing online PLC activities that help teachers develop as professionals and provide optimal support for students' learning. By continuing to enhance teachers' self-efficacy, they may provide the best service for students and help students succeed in learning. Keywords: self-efficacy, professional learning communities, primary mathematics teachers.